gas-forming pyomyositis in an immunocompetent patient: a case report and review - Jee Young Lee; Gyu Min Kong (Journal of International Medical Research)
The primary etiology of pyomyositis is predominantly Staphylococcus aureus , although Gram-negative bacteria may also be involved on rare occasions. The prognosis for pyomyositis caused by Gram-negative bacteria is more unfavorable than that of infections caused by Staphylococcus aureus. Among Gram-negative bacteria, members of the Enterobacteriaceae family, including Escherichia coli , Klebsiella species, and Salmonella species, have the capacity to produce gas. Gas-forming myositis is a rare phenomenon that primarily affects immunocompromised patients and is associated with a poor prognosis. To the best of our knowledge, no previous reports of gas-forming pyomyositis in an immunocompetent patient exist. We herein present the first documented case of Salmonella -induced gas-forming pyomyositis of the iliacus muscle in a healthy young man with no underlying diseases or comorbidities. Additionally, we reviewed cases of gas-forming pyomyositis in the literature and cases of pyomyositis caused by Gram-negative bacteria in immunocompetent patients.